Structural Analysis of The BRI Branch Office in Kesambi Sub-District Cirebon City - Rahmatulloh, Muhammad; Al-Aufa, Muhammad Fikri; Ray, Devana; Roesdiana, Tira (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
Safe and standardized infrastructure development is an important factor in supporting economic growth, especially in disaster-prone areas such as Cirebon. This research aims to analyze the structural strength of the BRI branch office building in Kesambi, Cirebon, in accordance with SNI 2847:2019, SNI 1726:2019, and SNI 1727:2020 regulations. This research uses a quantitative approach with ETABS V18.1.1 software to conduct structural analysis. The data used includes primary data from field measurements and secondary data from literature and applicable design standards. The analysis process includes structural modeling, load calculation, and strength evaluation of structural elements such as columns, beams, and slabs. The analysis results show that most of the building's structural elements meet the established strength standards. However, columns K1C, K2, and KT3 did not meet the Strong Column Weak Beam (SCWB) criteria, indicating the need for improvement in the design and strengthening of these elements. These findings indicate the importance of applying comprehensive structural analysis in the planning of banking buildings. The research also provides recommendations for design improvements to enhance the safety and structural durability of the building, and emphasizes the need for compliance with applicable regulations in infrastructure development. This study concludes that the BRI branch office building in Kesambi, Cirebon, is generally safe for use, but there are some elements that require more attention to ensure structural safety.